A dynamic modeling tool to anticipate the effectiveness of invasive plant control and restoration recovery trajectories in South African fynbos - Hall, Stuart A.; Bastos, Rita; Vicente, Joana; Vaz, Ana Sofia; Honrado, João P.; Holmes, Patricia M.; Gaertner, Mirijam; Esler, Karen J.; Cabral, João Alexandre (Restoration ecology, 2021)
Invasive alien plants negatively impact ecosystems, necessitating intricate management actions. In a critically endangered vegetation type within the fynbos biome of South Africa, a study was performed comparing different management interventions over plots invaded by Acacia saligna. A dynamic modeling approach was designed to analyze field data and simulate the effectiveness of several restoration methods. Field data for vegetation recovery rates over the course of 2 years were fed into the model, which allowed the extrapolation of multiple recovery trajectories over a long time‐span, not possible to obtain from traditional short‐term field surveys. Our model simulations show that different treatments in similarly degraded states at the time of clearing can result in vastly different recovery trajectories. Active seed sowing was initially most expensive but resulted in the most successful native shrub recovery, decreasing costs of longer‐term follow‐up acacia clearing. Clearing without burning was cheapest but resulted in limited establishment of both native and acacia cover, providing an opportunity for secondary invasion by alien forbs. In this case, biotic thresholds may have been crossed which prevented recovery of certain vegetation components. Active sowing can partially reverse thresholds by restoring shrub cover but not structural diversity. Therefore, even applying this treatment did not resemble vegetation structure of the reference condition after an extended period of 30 years, but does show how restoration can be improved by native seed sowing compared to passive restoration alone. Our model simulations provide a useful tool to support decision‐making by providing management recommendations for optimizing alien plant‐clearing protocols.